2022
DOI: 10.3390/molecules27020555
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Immune-Boosting Functions of Vitamins and Minerals as Nutritional Food Bioactive Compounds: A Comprehensive Review

Abstract: Food components have long been recognized to play a fundamental role in the growth and development of the human body, conferring protective functionalities against foreign matter that can be severe public health problems. Micronutrients such as vitamins and minerals are essential to the human body, and individuals must meet their daily requirements through dietary sources. Micronutrients act as immunomodulators and protect the host immune response, thus preventing immune evasion by pathogenic organisms. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 247 publications
(183 reference statements)
0
30
0
2
Order By: Relevance
“…Minerals are of paramount importance in order to preserve and obtain good health and their key role is supported by a significant amount of literature [ 3 ]. The crucial role of minerals shifts from helping vitamin absorption [ 4 ] and immunomodulatory effect [ 5 ] to metabolic [ 6 ] and bone metabolism [ 7 ], influencing hematological [ 8 ] and endocrine function [ 9 ]. The source of many important minerals is mainly plant-based therefore it is important to use a balanced diet to provide the adequate proportion of minerals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Minerals are of paramount importance in order to preserve and obtain good health and their key role is supported by a significant amount of literature [ 3 ]. The crucial role of minerals shifts from helping vitamin absorption [ 4 ] and immunomodulatory effect [ 5 ] to metabolic [ 6 ] and bone metabolism [ 7 ], influencing hematological [ 8 ] and endocrine function [ 9 ]. The source of many important minerals is mainly plant-based therefore it is important to use a balanced diet to provide the adequate proportion of minerals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TLR4 suppression prevented the GLE-mediated production of immunomodulators as well as activation of the p38, JNK, and NF-κB transcriptional factors. Together, our findings revealed that the TLR4-MAPK/NF-κB-signaling pathways were involved in GLE-induced macrophage activation and that GLE might be developed as a potential immunomodulatory functional food ingredient [ 122 , 123 ].…”
Section: Health Benefits and Risks Of Lettucementioning
confidence: 98%
“…Resveratrol is a polyphenol that is found in the extract of Vitis vinifera [ 149 ]. It possesses a wide range of bioactivities, including hepatoprotective, anti-cancer, anti-inflammatory, immunomodulatory, antidiabetic, and other properties [ 132 , 150 , 151 ]. In many rodent models, resveratrol has been shown to treat diabetes [ 152 , 153 ] and its complications [ 154 , 155 , 156 , 157 , 158 , 159 ].…”
Section: Phytogenic Compoundsmentioning
confidence: 99%